ENTREPRENEURIAL ORIENTATION CHANGE PRACTICES AND PERFORMANCE OF SELECTED REGISTERED SMES IN LAGOS STATE, NIGERIA. (Journal of the Management Sciences, 2024)
The development of nation’s economy is critical to its ability of developing strategies that exploit opportunities and managerial philosophies uniqueness in decision making, the growing diversity and enthusiasm of interest among businessmen and academics, particularly in the transforming procedures with an entrepreneurial orientation has become great concern. The study investigates how changing entrepreneurial oriented practices utilizing a cross sectional survey affected the performance amongst the four selected top grocery registered SMEs (Jendol superstore, Just-rite superstore, Addide stores, and KD Foods) operating in Ikorodu, division of Lagos State, Nigeria. Questionnaire was administered as a source of data collection to 100 respondents among staff of not less than three (3) years of employment engagement as the sample size, proportionally selected from the study focus. Pearson correlation statistical tool was adopted for data analysis. The study reveals that, innovativeness and risk-taking of business have a highly significant impact on SMEs performance; with pro-activeness having a weak, but positive relevance on SMEs performance. In conclusion, to improve and optimize entrepreneurial orientation change practices and adapt to future threatening changes, firm’s need to strengthened desire of healthy competitions, identifying and targeting weakness of competitors. It is recommended that, more innovativeness be sought after as guiding principles for capability and adaptability to handle the complexity of the ever- changing business surrounding, while involvement in risk- taking need be adopted with inevitable zeal and willingness to attain organizational growth and improved performance. Pro-activeness should be given adequate consideration to maintain and surpass existing performance as opportunities come but once. Despite study limitations, future researchers may need to enlarge sample size and create intense awareness on SMEs generally.
Keywords: Change, Entrepreneurial orientation, Performance, Practices, SMEs.